Climate Change Impact and Adaptation Study for Bangkok Metropolitan Region : Final Report - World Bank (World Bank, 2012)
This report is the primary output from the climate change impact and adaptation study for the Bangkok Metropolitan Region (BMR) produced for the Bangkok Metropolitan Administration (BMA) with financial support provided by the World Bank. The report concerns climate change, and provides an analysis of climate change impacts and adaptation options for the BMR. In addition to the more general matters on the physical setting and socioeconomics of BMR, the report considers a number of issues related to climate change in detail. These are: changes in the inundation pattern, and impact on the population and socioeconomics, and coping mechanisms to deal with the changed situation.